Cases on online discussion and interaction : experiences and outcomes - Aitken, Joan E.; Shedletsky, Leonard , 1944- (Gale virtual reference library, 2010)
"This book gives readers a better idea of what is likely to facilitate discussion online, what is likely to encourage collaborative meaning-making, what is likely to encourage productive, supportive, engaged discussion, and what is likely to foster critical thinking"--Provided by publisher